Formation of a Neuronal Membrane Model: A Quartz Crystal Microbalance with Dissipation Monitoring Study - Elaheh Kamaloo; Terri A. Camesano; Ramanathan Nagarajan (Biomolecules)
Supported lipid bilayers (SLBs) that model neuronal membranes are needed to explore the role of membrane lipids in the misfolding and aggregation of amyloid proteins associated with neurodegenerative diseases, including Parkinson’s and Alzheimer’s disease. The neuronal membranes include not only phospholipids, but also significant amounts of cholesterol, sphingomyelin, and gangliosides, which are critical to its biological function. In this study, we explored the conditions for the formation of an SLB, for the five-component lipid mixture composed of zwitterionic 1,2-Dioleoyl-sn-glycero-3-phosphocholine (DOPC), anionic 1,2-dioleoyl- sn-glycero-3-phospho-L-serine (DOPS), nonionic cholesterol (Chol), zwitterionic sphingomyelin (SM), and anionic ganglioside (GM), using the quartz crystal microbalance with dissipation monitoring (QCM-D) technique, by varying experimental parameters such as pH, buffer type, temperature, vesicle size, and osmotic stress. SLB formation from this multicomponent lipid system was found challenging because the vesicles adsorbed intact on the quartz crystal and failed to rupture. For most of the variables tested, other than osmotic stress, we found no or only partial vesicle rupture leading to either a supported layer of vesicles or a partial SLB that included unruptured vesicles. When osmotic stress was applied to the vesicles already adsorbed on the surface, by having a different salt concentration in the rinse buffer that follows vesicle flow compared to that of the dilution buffer during vesicle flow and adsorption, vesicle rupture increased, but it remained incomplete. In contrast, when osmotic stress was applied during vesicle flow and adsorption on the surface, by having different salt concentrations in the dilution buffer in which vesicles flowed compared to the hydration buffer in which vesicles were prepared, complete vesicle rupture and successful formation of a rigid SLB was demonstrated. The robustness of this approach to form SLBs by applying osmotic stress during vesicle adsorption was found to be independent of the number of lipid components, as shown by SLB formation from the 1-, 2-, 3-, 4-, and 5-component lipid systems.